The Family’s Roles in the Effects of Working from Home During the Covid-19 Pandemic on Children (A Case Study of Families in Banda Aceh City) - Ayu, Rizqa Febry; Kiramang, Khaeruddin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The increasing prevalence of the Covid-19 virus has a significant impact on children's activities, particularly in the realm of education, resulting in the necessity of learning at home. In addition to having an effect on children due to atypical learning patterns, this is the responsibility of the family to facilitate children's education. To prevent learning loss for children, families must play a significant role in promoting learning. This study examines the influence of family on the effects of working from home on children during the influenza pandemic. To determine the results of the family's function, this research combines an empirical methodology with qualitative methods, namely direct and online interviews. Although the effects of working from home resulted in tedium, lack of discipline, laziness, difficulty in advising, emotional instability, stress on children, and a lack of supportive facilities, they affected the family economy. However, the family's role in allowing children to work from home is successful, there is no neglect of children even though the mentoring process will not be achieved, and parents continue to develop, foster, and accompany learning so that children continue to develop and be creative despite the pandemic.